"What shall we do with Germany?" The public debate in the United States on the future of postwar Germany. - Combes-Neufeld, Elizabeth. (University of Ottawa (Canada), 1997)
During World War II, the American foreign policy opinion elites conducted an intense debate in the popular and academic presses on the problem of how to treat the people of Germany. Taking place during a war conducted by a democracy against a totalitarian regime and coinciding with the introduction of scientific public opinion measurement, the debate emphasised American democratic ideology. The participants in the debate, from government officials to journalists, often constructed their arguments around national character theories which allowed them to proceed rapidly to the conclusion that the whole German people bore the blame for the war. On this basis these commentators outlined plans to both permanently curb German aggression and to bring democracy to Germany. These developments fostered impractical public expectations for foreign policy achievements and drove the public debate on the German problem to extremes which found their way into policy planning. These extremes precipitated an elitist reaction that presaged the development of the postwar realist approach to foreign policy, including its emphasis on planning by experts and its concomitant dismissal of mass public opinion. This approach is apparent in the pollsters' wartime analyses of mass public opinion on the German question.
Keywords: Political Science, General.